Trust and Workplace Performance - T. Addison, John (2020)
Using European Company Survey data, this paper explores the relationship between trust and establishment performance under two different types of workplace representation, works councils on the one hand and union bodies on the other. Trust is initially measured using the individual survey respondent’s assessment of the ‘contribution’ of the other side, the rating of the employee representative being favoured over that of management as less subject to feedback from performance. Although the potential endogeneity of employee trust in management is modelled, a preferred inverse measure of trust (or dissonance) is then constructed from the discrepancy between the assessments of the two sides of the quality of workplace industrial relations. Employee trust is associated throughout with improved establishment performance, and conversely for the dissonance counterpart. In their presence, there is no suggestion that one type of workplace representation is superior to another. Simply put, good industrial relations trumps institutional form.